Lipid biosignature of breast cancer tissues by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry - Silva, Catarina L. (2022)
Purpose One of the hallmarks of cancer cells is the demand of supply for the synthesis of new membranes involved in cell proliferation and lipids have an important role in cellular structure, signaling pathways and progression of cancer. In this sense, lipid studies have become an essential tool allowing the establishment of signatures associated with breast cancer (BC). In this regard, some metabolic processes including proteins, nucleic acids and lipid synthesis are enhanced as part of cancer-associated metabolic reprogramming, as a requirement for cell growth and proliferation. Methods Pairwise samples of breast active carcinoma (BAC) and breast cancer-free tissues were collected from n=28 patients and analyzed by MALDI-TOF MS. Results Major lipid species are identifed in the MALDI-TOF mass spectra, with certain phosphatidylinositols (PIs) detect able only in BAC. Statistical analysis revealed signifcant diferences (p<0.05) between ratios lysophosphatidylcholine (LPC) 16:0/phosphatidylcholine (PC) 16:0_18:2 between AC and CF groups as well as for BC stages II and III. The ratio PC 16:0_18:2/PC16:0_18:1 was statistically diferent between AC and CF groups. The one-way ANOVA revealed that there are no statistical diferences among BC stages (I, II and III) within AC group. Comparing BC stages, the signifcance impact increased (p<0.05) with stage. Conclusion The obtained data revealed MALDI-TOF MS as a powerful tool to explore lipid signatures and the enzyme activity associated with BC and possibly establish novel disease markers.